Diagnostic and Monitoring Serology in Commercial Poultry Integrations: Practical Applications - Gary D. Butcher (EDIS)
Serologic testing is an important tool used in the commercial poultry industry for diagnosis of disease and monitoring of flock health. However, the proper methods for serologic testing are often not understood. It is essential to know the uses and limitations of this procedure to ensure maximum benefit is realized. This document is VM137, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 2, 2002.